Technology as a Pedagogical Strategy in South African Higher Education Institutions - Masenya, Malesela Jim; Maloa, Mmakgosi Precilla (Universitas Medan Area, 2024)
The purpose of this paper is to discuss the challenges of employing Information and Communication Technologies (ICTs) and its impacts on all sectors of society, including the education sector. Transfer of knowledge, which is one of the foundations of learning, is among the most fundamental social achievements of human beings. The concept of moving the traditional classroom of desks, notebooks, pencils, and blackboard to an online forum of computers, software, and the internet intimidates many teachers who are accustomed to the face-to-face interaction of the traditional classroom. Education is viewed as one of the key mechanisms of achieving social transformation. Although educational challenges demand multi-pronged approaches, which may include both traditional teaching approaches and innovative non-digital instructional designs, it is the role of educational technology that is the focus of this paper. South African higher education has considerable strengths. In several areas of learning and teaching, its institutions offer academic programs that produce high-quality graduates with knowledge, competencies, and skills to practice occupations and professions anywhere in the world. It is in this educational context that new opportunities for educational technology have arisen. The paper argues that online education provides an environment where all and often marginalized voices can be heard and also contribute to higher participation of students as well as collaborative learning. The paper concludes that educational technology has a key role to play in South African higher education as one of the strategies for addressing teaching and learning concerns.